Discovery of dome-shaped superconducting phase and anisotropic transport in a van der Waals layered candidate NbIrTe₄ under pressure - Jin, Meiling (2021)
The unique electronic structure and crystal structure driven by external pressure in transition metal tellurides (TMTs) can host unconventional quantum states. Here, the discovery of pressure-induced phase transition at ≈2 GPa, and dome-shaped superconducting phase emerged in van der Waals layered NbIrTe4 is reported. The highest critical temperature (Tc ) is ≈5.8 K at pressure of ≈16 GPa, where the interlayered Te-Te covalent bonds form simultaneously derived from the synchrotron diffraction data, indicating the hosting structure of superconducting evolved from low-pressure two-dimensional (2D) phase to three-dimensional (3D) structure with pressure higher than 30 GPa. Strikingly, the authors have found an anisotropic transport in the vicinity of the superconducting state, suggesting the emergence of a "stripe"-like phase. The dome-shaped superconducting phase and anisotropic transport are possibly due to the spatial modulation of interlayer Josephson coupling .